Primary Squamous Cell Carcinoma of the Gallbladder: Case Report - Sahar Dashti; Maryam Garousi; Elahe Mirzaee; Navid Abdi; Mastaneh Sanei (Clinical Case Reports)
ABSTRACT Pure gallbladder squamous cell carcinoma is rare. Adenocarcinoma is the foremost malignant pathology of gallbladder cancer. Simultaneously, squamous cell carcinoma accounts for only 1% of malignant gallbladder tumors. They are often advanced at diagnosis and associated with a poor prognosis. The patient was a 37‐year‐old man diagnosed with poorly differentiated squamous cell carcinoma of the gallbladder. Cholecystectomy, right hemicolectomy, hepatic wedge resection, and regional lymph node dissection were performed, and then he received six courses of adjuvant chemotherapy with the FOLFOX regimen. After 2 months, liver metastasis was diagnosed, and a chemotherapy regimen consisting of gemcitabine, cisplatin, and pembrolizumab was started. After three courses, stable disease was seen. Surgery is the main treatment. There is no consensus about the best adjuvant treatment. The results obtained from this patient might help elucidate the role of adjuvant therapies in treating this rare case report.